1982
DOI: 10.1152/jappl.1982.52.1.231
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism by which positive end-expiratory pressure increases cerebrospinal fluid pressure in dogs

Abstract: We investigated possible mechanisms by which positive end-expiratory pressure (PEEP) increased cerebrospinal fluid pressure (PCSF) in anesthetized mechanically ventilated dogs. In part I of the study, PEEP was applied in 5 cmH2O increments each lasting 1-2 min, before and after a snare separated the spinal from the cerebral subarachnoid space in each animal. Next, with the spinal cord still ligated, the dogs were ventilated without PEEP while superior vena cava pressure (PSVC) was raised in 5 cmH2O increments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 0 publications
1
17
0
2
Order By: Relevance
“…In addition, why are women more commonly a¤ected than males given that the proposed mechanism is increased intraabdominal pressure and males tend to have more central obesity compared to females. 139 Venous Obstruction and Pseudotumor Cerebri Syndrome Experimentally, Luce et al [104] demonstrated that in anaesthetized dogs, an increase in pleural pressure increases lumbar and intracranial CSF pressure. This increase in CSF pressure was secondary to elevation of venous pressure in the superior vena cava.…”
Section: Non Obstructive Venous Hypertensionmentioning
confidence: 99%
“…In addition, why are women more commonly a¤ected than males given that the proposed mechanism is increased intraabdominal pressure and males tend to have more central obesity compared to females. 139 Venous Obstruction and Pseudotumor Cerebri Syndrome Experimentally, Luce et al [104] demonstrated that in anaesthetized dogs, an increase in pleural pressure increases lumbar and intracranial CSF pressure. This increase in CSF pressure was secondary to elevation of venous pressure in the superior vena cava.…”
Section: Non Obstructive Venous Hypertensionmentioning
confidence: 99%
“…Increased intracranial pressure during ventilation with positive end-expiratory pressure has been attributed to passive elevation in IJ venous pressure. 8 The competency of the IJ valve has been previously tested by IJ venography during Valsalva maneuver or cough, 5 a Doppler sample of the IJ vein flow combined with M-mode ultrasonography of the IJ valve during Valsalva,9 and color flow imaging ( CFI) of the IJ vein. 10 However, IJ venography is invasive, with some associated risk, while it is difficult to interpret Doppler and CFI data of the IJ vein due to slow and swirling flow.…”
mentioning
confidence: 99%
“…Our results were similar to the findings of Kranz et al (2015), though they used abdominal circumference instead of BMI to represent body habitus. A large number of previous studies, both clinical and experimental, suggested that central obesity raised intracranial pressure (ICP) by increasing intraabdominal pressure, leading to increased cardiac filling pressure and intracranial venous pressure, hindering cerebral venous drainage (Greer, 1962;Luce et al, 1982;Bloomfield et al, 1995;Sugerman et al, 1997). Adipose tissue is considered to be a neuroendocrine tissue releasing adipokines, especially leptin.…”
Section: Discussionmentioning
confidence: 99%